Botulinum toxin in the facial paralysis (Research, Society and Development, 2023)
Botulinum toxin is widely used in orofacial harmonization due to its aesthetic and therapeutic benefits. When applied correctly, it smooths facial wrinkles, improves facial contours, and treats conditions such as bruxism, gummy smile, and chronic migraines. Its temporary and reversible action makes it safe to improve the facial appearance and quality of life for patients. The mechanism of action of botulinum toxin involves blocking the release of the neurotransmitter acetylcholine, interrupting communication between nerves and muscles, resulting in localized muscle relaxation. Although temporary, the effect can be beneficial and nerve endings can regenerate over time. In addition, botulinum toxin is effective in the treatment of facial paralysis, improving facial symmetry, smoothing wrinkles and helping to recover muscle function. However, its use must be carried out by trained professionals, who will evaluate each case individually and follow safety protocols to obtain the best possible results. Thus, the objective of this narrative review of the literature is to analyze and gather scientific evidence on the use of botulinum toxin in orofacial harmonization and in the treatment of facial paralysis.